Introduction to drawing systems - Barnstone, Myron; The Barnstone Studios (Estados Unidos); 3Seed Marketing & Design Studio (USA : The Barnstone Studios, 2014)
Es un serie de diez lecciones sobre los fundamentos del dibujo y el diseño en un aula dirigida por Myron Barnstone en su "One-man-school" sobre dibujo
Introduction to drawing systems: (Disc 1. Lesson 1. Introduction to drawing systems : the two-dimensional elevation ; Lesson 2. The two-dimensional still life arrangement--Disc 2. Lesson 3. The construction and truncation of a sphere ; Lesson 4. The construction of three-dimensional forms--Disc 3. Lesson 5. The sphere in value ; Lesson 6. The value zone system applied to a still life--Disc 4. Lesson 7. Introduction to the root two rectangle ; Lesson 8. The plant assignment--Disc 5. Lesson 9. The portrait ; the geometry of the human head ; Lesson 10. An overview of dynamic symmetry : the rectangles--Drawing 1 Extra (CD)
Keywords: DIBUJO -- ESTUDIO Y ENSEÑANZA; DIBUJO -- TECNICAS; DIBUJO -- METODOS; PROPORCION (ARTE); FORMA (ESTETICA)